DO ALL TRADITIONAL RISK FACTORS ASSOCIATE SAME WITH MORTALITY IN SENIOR POPULATION? - A. E. Imaeva; S. A. Shalnova; Yu. A. Balanova; A. V. Kapustina; G. A. Muromtseva; S. E. Evstifeeva; A. D. Deev; V. M. Shkolnikov (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To evaluate the impact of traditional risk factors (RF) to overall and cardiovascular mortality of the population ≥75 year old.Material and methods. The results are acquired in the prospective cohort study “Stress, ageing and health”. Totally, 455 Moscovites assessed, age ≥75 y.o. The traditional RF were evaluated: arterial hypertension, smoking, obesity and dyslipidemia. The follow up on mortality lasted for 8 years. Totally, 239 deaths registered, of those 169 cardiovascular. Statistics was done with STATA 14.1.Results. After stratification by sex and age, with the mortality from all cases in the 75-79 y.o. cohort, only current smoking status associated significantly (p=0,0001), and with cardiovascular mortality — current smoking and abdominal obesity, with relative risks 2,91 and 1,92, respectively. Also, in the ≥80 y.o. group, there were no RF influencing significantly the mortality.Conclusion. Among all traditional RF, in the age strata 75-79 y.o., only current smoking associated significantly with the all-cause mortality, and with cardiovascular — also abdominal obesity. Among the persons of ≥80 y.o., traditional RF lose their impact for both all-cause and cardiovascular mortality.